2012
DOI: 10.1007/s12663-012-0447-6
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Joint Arthrocentesis for Internal Derangement with Disc Displacement Without Reduction

Abstract: Temporomandibular joint (TMJ) disc derangement is defined as a malpositioning of the articular disc relative to the condyle and eminence. Arthrocentesis of the TMJ is a minimally invasive chair side procedure for the patients with TMJ internal derangement. This case report presents convincing results to keep arthrocentesis as an imperative procedure to relieve such patients of their acute symptoms. TMJ dynamics has also been discussed for an in-depth understanding of the pathology in cases with internal derang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 9 publications
0
20
0
3
Order By: Relevance
“…Since the introduction of arthrocentesis, the indication range for this procedure has broadened34910. Since arthrocentesis is a minimally invasive surgical procedure, it is preferred for the treatment of ID of the TMJ10111819.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the introduction of arthrocentesis, the indication range for this procedure has broadened34910. Since arthrocentesis is a minimally invasive surgical procedure, it is preferred for the treatment of ID of the TMJ10111819.…”
Section: Discussionmentioning
confidence: 99%
“…They cause various joint symptoms, most frequently limitations in and pain during mouth opening, and may also lead to degenerative changes in the cartilage and bone structures of the joint123. The most frequent cause of TMJ dysfunction is internal derangement (ID), which refers to alteration of the joint's normal path of motion, largely involving the function of the articular disc134. The severity of ID is assessed using the Wilkes classification, which consists of five stages ranging from symptom-free slight forward displacement to degenerative arthritic changes accompanied by severe symptoms5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lavage of the upper joint space reduces pain by removing inflammation mediators from the joint , increasing mandibular mobility by removing intra-articular adhesions, eliminating the negative pressure within the joint, recovering disc and fossa space, and improving disc mobility, which reduces the mechanical obstruction caused by the anterior position of the disc .the results of arthrocentesis were in agreement with studies. [20,24,25] Analysing results of clicking sound in study groups indicated beneficial effect of both treatment modalities in reducing clicking with no statistical significant difference between them. The effect of arthrocentesis in on the clicking sound has been reported in a lot of publication to reduce joint pain, improve function, and reduce clicking as the arthrocentesis is considered an evident method to treat TMJ disc derangement .…”
Section: Discussionmentioning
confidence: 91%
“…Arthrocentesis has been indicated as an effective treatment approach in patients with DDWOR [ 1 , 5 7 , 14 ]. Regarding the possible variations, the literature seems inconclusive when evaluating the different single puncture arthrocentesis techniques such as using two needles' fusion to one puncture devise [ 15 ] or using additional sodium hyaluronate with arthrocentesis [ 3 ].…”
Section: Discussionmentioning
confidence: 99%